Preventing Bullying in Schools: A Case Study of Restorative Justice Implementation and Counseling Service Management - Ferna Delisi; Sudarwan Danim; Muhammad Kristiawan (Journal of Social Work and Science Education, 2026)
This study examines efforts to prevent bullying cases in junior high schools through the implementation of restorative justice approaches and guidance and counseling (GC) service management. The aim is to investigate the factors causing bullying, the effectiveness of GC service management, the applicability of restorative justice, and challenges faced by schools in preventing bullying. Using a qualitative case study method, data were collected from SMP Negeri 1 Kepahiang, Indonesia, through open-ended questionnaires, observations, and document analysis involving principals, GC teachers, students, and parents. Results revealed that bullying stems from both internal factors (personality, emotional intelligence) and external factors (family environment, peer pressure, social media influence). The GC service management system effectively implements preventive services through classroom guidance and responsive services through individual counseling and mediation. Restorative justice successfully resolves verbal, social, and minor cyberbullying cases by fostering dialogue and reconciliation between perpetrators and victims. However, severe physical bullying, sexual harassment, and severe cyberbullying require legal intervention beyond restorative approaches. The novelty of this research lies in examining the integration of restorative justice within Indonesian school counseling systems. Practical implications suggest that schools should strengthen anti-bullying policies, enhance GC teacher competencies, establish safe reporting mechanisms, and develop clear standard operating procedures distinguishing cases suitable for restorative justice from those requiring legal action. This study contributes to educational administration literature by providing empirical evidence on holistic bullying prevention strategies in the Indonesian context.